BATHYAL FISH OTOLITHS FROM THE BARTONIAN (EOCENE) OF THE TURIN HILL (PIEDMONT, ITALY) - Werner Schwarzhans; GIORGIO CARNEVALE (Rivista Italiana di Paleontologia e Stratigrafia, 2022)
A small collection of fish otoliths, mostly myctophids, from a bathyal environment are described from the Bartonian (late middle Eocene) Marne di Monte Piano Formation of San Genesio, Turin Hill, Piedmont. Myctophids have been rarely recorded from the Eocene in general, and few bathyal environments have been sampled for otoliths of that time interval globally. In this context, the assemblage described herein fills an important stratigraphic gap in the record and evolution of the Myctophidae. The findings are discussed in a regional and stratigraphic context. Seven species are recorded, of which one is new,  Oligophus bartonensis n. sp., belonging to the family Myctophidae.